Features of the functioning of innate immunity in children with chronic idiopathic urticaria - S. V. Maltsev; L. P. Sizyakina; A. A. Lebedenko (Бюллетень сибирской медицины)
Aim. To study the features of the functioning of innate immunity in children with chronic idiopathic urticaria.Materials and methods. The study included 28 children of both sexes aged 6–16 years with chronic idiopathic urticaria (CIU). The median age of the patients was 8 years (p = 0.045). Clinical research methods included an analysis of complaints and anamnestic data, as well as an objective examination of the child (dynamics of urticaria, severity of itching, the presence of angioedema). Immunological techniques included determination of the number of monocytes expressing CD14+CD282+, CD14+CD284+, CD14+CD289+, the number of peripheral blood lymphocytes expressing CD3+CD16+, the levels of immunoglobulin (Ig) E, lactoferrin, interferon (IFN) γ, interleukin (IL)4, and IL-6, and a nitroblue tetrazolium test.Results. In the course of the study, an increase in the expression of Toll-like receptors TLR2 and TLR4 by monocytes, a decrease in the expression of TLR9 by monocytes, a significant rise in lactoferrin levels, a slight decrease in the number of natural killer (NK) cells, a decrease in microbicidal activity and adaptive reserves, a rise in IgE levels, a decrease in IL-4 levels, and an increase in IFNγ and IL-6 were revealed in children with CIU.Conclusion. The immunological changes revealed during the study indicate multidirectional expression of Toll-like receptors, disturbances in the work of the cellular components of innate immunity, and a launch of a proinflammatory cytokine cascade in children with CIU, which can serve as a mainstay for the development of new schemes for personalized therapy of CIU in children.